Sustaining thermal power plant production in low water supply regions using cooling towers - Al-Kayiem, H.H. (WITPress, 2014)
Climate and geographical changes are among many other reasons causing water depletion. This may cause reduction in water resourcing from rivers and lakes to cool existing or planed thermal power plants. The present paper presents an alternative way to treat the water shortage problem by using cooling towers. The paper presents the design and analysis of a closed cooling system for a 200 MW thermal power plant with a partial addition from the natural resources of 10, 20, 30, and 40 mixing ratios. The hydrothermal process of the condenser and the cooling tower were modelled and solved computationally using weather data of Baghdad. Two types of cooling towers have been investigated using different types of locally made fills. The procedure has been validated using in-service power plant data. An interesting finding from the numerical analyses of the cooling tower indicated that there is an optimum size for the cooling tower for best performance. It is recommended to design the cooling system with a 15 to 25 mixing ratio. Cross flow cooling tower was able to produce cooling water with 1oC compared to the cross flow cooling tower. Â© 2014 WIT Press.